Direct simulation of hypertensive stress on endothelial cells: a streamlined model of in-vitro-hypertension - Raschi, Elena; Bodio, Caterina; Brullo, Chiara; Parati, Gianfranco; Meroni, Pier Luigi; Borghi, Maria Orietta; Calvillo, Laura (Frontiers in Physiology, 2026)
Hypertension stands as one of the most significant preventable risk factors for cardiovascular disease, which is the leading cause of mortality worldwide. There is a disturbing gap, in preclinical research, between simplified cell culture and complex in vivo models. To contribute to bridge this gap, we have developed a simplified but realistic in vitro dynamic model of hypertension allowing the discrimination between mechanical pressure effects and Angiotensin II’s pharmacological action. We utilized an advanced bioreactor system capable of producing adjustable flow rates to culture human umbilical vein endothelial cells (HUVEC). This system allows for the investigation of the possible effects of Angiotensin II and/or an increase in intraluminal pressure (via the Live-Pa pressure-actuation device) exerted directly upon the HUVEC monolayer without simulating transmural pressure. Key hypertension-associated inflammatory markers, such as NF-kB, p38MAPK, Interleukins (IL)-6/8, and Endothelin-1 (ET-1), were subsequently assessed. Angiotensin II induced HUVEC NF-kB and p38MAPK phosphorylation, and elevated IL-6 and ET-1 secretion, with a trend in IL-8 increase. Live-Pa alone enhanced NF-kB and p38MAPK and influenced cytokine/chemokine secretion. Combined stimuli significantly augmented the inflammatory parameters as compared to unstimulated cells, suggesting a synergistic effect between chemical and mechanical stimuli. Overall, these in vitro results demonstrate both key consistencies (e.g., NF-kB and p38MAPK activation) and specific distinctions (e.g., no significant IL-6 increase in Live-Pa-exposed versus control HUVEC) when compared to published data from hypertensive versus normotensive animal models. The proposed advanced in vitro model may successfully reproduce some features of vascular function in hypertension and simulate hemodynamic conditions by controlled flow with adjustable pressure parameters. Crucially, this system allows discrimination between mechanical blood pressure effects and Angiotensin II’s pharmacological action on the endothelium, paving the way for understanding pathophysiological mechanisms and developing new therapies. Established methods make it possible that studies on cultured endothelial cells will be better comparable to the results of in vivo studies, thus directly supporting the 3Rs framework—Replacement, Reduction, and Refinement—which is essential for high-standard and ethical research.